Influences of the compressibility on aerodynamic characteristics of profile under the transonic flow theory - Ngoc, Hoang Thi Bich (Vietnam Journal of Mechanics, 2007)
Transonic flows are complex problems. At certain Mach numbers, in gas flows there are local transitions from the subsonic into the supersonic and reciprocally, especially the discontinuity throughout shock waves. Subsonic flows and supersonic flows have very different properties, thus calculation methods are also different-the subsonic equation is elliptic and the supersonic equation is hyperbolic. Using established programs (based on the incompressible theory, the compressible theory and the transonic theory), we studied sub-transonic flow characteristics with variations of the Mach number. Our studies are also carried out with variations of incidence, which impact on t he transonic effect. Numerical results show that the local compressibility depends on not only the speed but also the incidence. At a rather great angle of attack, local supersonic regions can appear with free Mach numbers in the order of 0.3 - the Mach number is normally considered as a speed of incompressible flows. According to these results, we can recognize for which regime the local compressibility of flow is considerable and then it is necessary to consider the problem under the transonic flow theory